Signs and symptoms of pediatric complex regional pain syndrome - type 1: A retrospective cohort study. Issue 1 (31st December 2023) - Mesaroli, Giulia; McLennan, Logan; Friedrich, Yvonne; Stinson, Jennifer; Sethna, Navil; Logan, Deirdre
ABSTRACT: Background: Complex regional pain syndrome (CRPS) presents with an array of symptoms that can vary from child to child, making it difficult to diagnose and differentiate from other pain conditions such as chronic musculoskeletal (MSK) pain. Thirteen symptoms and signs are outlined in the Budapest criteria for CRPS (developed and validated for adults) but have not been well described in pediatrics. Aims: The aim of this study was to describe the signs and symptoms of pediatric CRPS type 1 (CRPS 1) and determine whether a cluster of symptoms can differentiate CRPS 1 from chronic MSK pain. Methods: A retrospective cohort study of pediatric patients with CRPS 1 and MSK pain in a pediatric pain program was conducted. Descriptive statistics were used to report demographics and pain characteristics. The chi-square test was used to evaluate differences in signs and symptoms between patients with CRPS and MSK pain. A logistic regression model was used to evaluate whether a cluster of symptoms could predict a diagnosis of CRPS 1. Results: The sample included 187 patients (99 with CRPS 1 and 88 with MSK pain); 81% were female with a mean age 14.1 years. The most prevalent CRPS symptoms were hyperalgesia (54%) and allodynia (52%). A cluster of symptoms (hyperalgesia, color changes, and range of motion) predicted the probability of a diagnosis of CRPS 1. Conclusions: A cluster of symptoms may be critical in differentiating pediatric CRPS 1 and MSK pain. Future research is needed to determine if this model is valid in external populations and to explore whether a similar model can differentiate CRPS 1 from other pain conditions (e.g., neuropathic pain).